PENGARUH CITRA MEREK, PERSEPSI HARGA DAN PROMOSI MELALUI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK HIJAB UMAMA GALLERY PALEMBANG - Laracia, Melsa; Hartini, Titin; Asrol, Safitri (Jurnal Ekonomi dan Bisnis Nias Selatan, 2026)
This study aims to analyze the effects of brand image, price perception, and social media promotion on purchasing decisions for Umama Gallery hijab products in Palembang. The study employed a quantitative survey approach. The research population consisted of 31,273 consumers, while the sample was determined using incidental sampling based on the Taro Yamane formula with a 5% margin of error, resulting in 395 respondents. Primary data were collected through a five-point Likert-scale questionnaire and were analyzed using IBM SPSS Statistics 29. Prior to hypothesis testing, the data met the validity, reliability, and classical assumption requirements. The results show that brand image, price perception, and social media promotion each have a positive and significant effect on purchasing decisions. Among these variables, price perception has the strongest influence, followed by brand image and social media promotion. Furthermore, all three variables simultaneously have a significant effect on purchasing decisions. The coefficient of determination (R² = 0.438) indicates that brand image, price perception, and social media promotion explain 43.8% of the variance in purchasing decisions, while the remaining 56.2% is explained by other factors beyond the scope of this study.